Process overview: development of NICE guidelines. Issue 2 (February 2017) - Ogden, Joy
Abstract : Developing NICE guidelines is a complex and involved procedure. This article provides an overview of the whole process from start to finish, including an inside view from a former NICE guideline committee chair.